Impact of seasonal hydrological variation on the distributions of tetraether lipids along the Amazon River in the central Amazon basin: implications for the MBT/CBT paleothermometer and the BIT index - Zell, Claudia; Kim, Jung-Hyun; Abril, Gwenaël; Sobrinho, Rodrigo; Dorhout, Denise; Moreira-Turcq, Patricia; Sinninghe Damsté, Jaap (Frontiers in Microbiology, 2013)
Suspended particulate matter (SPM) was collected along the Amazonian rivers in the central Amazon basin and in three tributaries during the rising water (RW), high water (HW), falling water (FW) and low water (LW) season. Changes in the concentration and the distribution of brGDGTs, i.e. the methylation index of branched tetraethers (MBT) and the cyclization of brGDGTs (CBT), were seen in the main stem Amazon. The highest concentration of core lipid branched glycerol dialkyl glycerol tetraethers (brGDGTs) normalized to particulate organic carbon was found during the HW season. During the HW season the MBT and CBT in the Amazon main stem was also most similar to that of lowland Amazon (terra firme) soils, indicating that the highest input of soil-derived brGDGTs occurs due to increased water runoff. During the other seasons the MBT and CBT indicated an increased influence of in situ production of brGDGTs even though soils remained the main source of brGDGTs. Our results reveal that the influence of seasonal variation is relatively small, but can be clearly detected. Crenarchaeol is mostly produced in the river. Its concentration was lower during the HW season compared to that of the other seasons. Hence, our study shows the complexity of processes that influence the GDGT distribution during the transport from land to ocean. It emphasizes the importance of a detailed study of a river basin to interpret the MBT/CBT and BIT records for paleo reconstructions in adjacent marine setting.